The effects of occupational exposure to chlorpyrifos on the peripheral nervous system: a prospective cohort study. Issue 3 (25th February 2004) - Albers, J W; Garabrant, D H; Schweitzer, S J; Garrison, R P; Richardson, R J; Berent, S
Abstract : Aims: To determine whether chronic occupational exposure to chlorpyrifos at levels associated with various aspects of manufacturing produced a clinically evident or subclinical peripheral neuropathy. Methods: Clinical and quantitative nerve conduction study (NCS) examinations were performed on two occasions on chlorpyrifos manufacturing workers who had measurable chlorpyrifos exposure and a referent group. Baseline evaluations were performed on 53 of 66 eligible chlorpyrifos subjects and on 60 of 74 eligible referent subjects; one-year evaluations were completed on 111 of the 113 subjects evaluated at baseline. Results: Chlorpyrifos and referent groups differed significantly in measures of 3, 5, 6 trichloro-2-pyridinol excretion and plasma butyrylcholinesterase (BuChE) activity, indicating substantially higher exposures among chlorpyrifos subjects. Few subjects had clinically important neurological symptoms or signs. NCS results were comparable to control values, and there were no significant group differences in NCS results at baseline, one year, or change over one year. No chlorpyrifos subject fulfilled conventional criteria for confirmed peripheral neuropathy at baseline or one-year examinations. The odds ratios for developing any diagnosable level of peripheral neuropathy among the chlorpyrifos subjects was not increased at baseline or at one year compared to referents at baseline. Mixed regression models used to evaluate subclinical group-by-time interactions showed numerous significant NCS differences attributable to near-nerve temperature differences among all subjects between the baseline and one-year examinations, but only a few disparate effects related to group. Conclusions: Chronic chlorpyrifos exposure during the manufacturing process sufficient to produce biological effects on BuChE activity was not associated with clinically evident or subclinical peripheral neuropathy at baseline or with measurable deterioration among chlorpyrifos subjects compared to referents after one year of additional exposure.